Characteristics and identification of sites of chagasic ventricular tachycardia by endocardial mapping - Távora,Maria Zildany P. (1999)
OBJECTIVE: To study electrophysiological characteristics that enable the identification and ablation of sites of chagasic tachycardia. METHODS: Thirty-one patients with chronic Chagas' heart disease and sustained ventricular tachycardia (SVT) underwent electrophysiological study to map and ablate that arrhythmia. Fifteen patients had hemodinamically stable SVT reproducible by programmed ventricular stimulation, 9 men and 6 women with ages ranging from 37 to 67 years and ejection fraction varying from 0.17 to 0.64. Endocardial mapping was performed during SVT in all patients. Radiofrequency (RF) current was applied to sites of presystolic activity of at least 30 ms. Entrainment was used to identify reentrant circuits. In both successful and unsuccessful sites of RF current application, electrogram and entrainment were analyzed. RESULTS: Entrainment was obtained during all mapped SVT. In 70.5% of the sites we observed concealed entrainment and ventricular tachycardia termination in the first 15 seconds of RF current application. In the unsuccessful sites, significantly earlier electrical activity was seen than in the successful ones. Concealed entrainment was significantly associated with ventricular tachycardia termination. Bystander areas were not observed. CONCLUSION: The reentrant mechanism was responsible for the genesis of all tachycardias. In 70.5% of the studied sites, the endocardial participation of the slow conducting zone of reentrant circuits was shown. Concealed entrainment was the main electrophysiological parameter associated with successful RF current application. There was no electrophysiological evidence of bystander regions in the mapped circuits of SVT.